The Outcome of Vitrectomy in Acute Postoperative Endophthalmitis - Sindy Boru Sembiring; Yulia Aziza; Gitalisa Andayani Adriono (International Journal of Retina, 2018)
Introduction: Twenty years ago, the results of Endophthalmitis Vitrectomy Study (EVS) were adapted worldwide as the standard management of endophthalmitis. The study suggested that there was no benefit of performing vitrectomy for acute postoperative endophthalmitis, unless for patients who presents with visual acuity of light perception. However, vitrectomy with advanced technology and technique has been changed rapidly in the last decades; therefore, we need to reconsider its role. We conducted a study and the purpose of our study was to describe the indications for vitrectomy and the outcomes in acute postoperative endophthalmitis at Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Methods: Our study was a descriptive-retrospective case series. We reviewed clinical and microbiological records of all patients with clinical diagnosis of acute postoperative endophthalmitis who underwent vitrectomy in Cipto Mangunkusumo Hospital between 2007 and September 2015. Presenting visual acuity, visual outcome and complications were described. Result: Our study was a descriptive-retrospective case series. We reviewed clinical and microbiological records of all patients with clinical diagnosis of acute postoperative endophthalmitis who underwent vitrectomy in Cipto Mangunkusumo Hospital between 2007 and September 2015. Presenting visual acuity, visual outcome and complications were described. Conclusion: An eight-year experience has taught us that vitrectomy offers better treatment outcome in the group with visual acuity of hand movement than those who only had visual acuity of light perception.